Mechanical ventilation induces brainstem inflammation in preterm fetal sheep - Vidinopoulos, Kayla; Azman, Zahrah; Somers, Ainsley; Zahra, Valerie A.; Thiel, Alison; Lu, Hui; Pham, Yen; Tran, Nhi Thao; Allison, Beth J.; Herlenius, Eric; Hooper, Stuart; Galinsky, Robert; et al. (Frontiers in Pediatrics, 2023)
Background Preterm infants have immature respiratory drive and often require prolonged periods of mechanical ventilation. Prolonged mechanical ventilation induces systemic inflammation resulting in ventilation-induced brain injury, however its effect on brainstem respiratory centers is unknown. We aimed to determine the effects of 24 h of mechanical ventilation on inflammation and injury in brainstem respiratory centres of preterm fetal sheep. Methods Preterm fetal sheep at 110 ± 1 days (d) gestation were instrumented to provide mechanical ventilation in utero. At 112 ± 1 d gestation, fetuses received either mechanical ventilation (VENT; n = 7; 3 ml/kg) for 24 h, or no ventilation (CONT; n = 6). At post-mortem, fetal brainstems were collected for assessment of mRNA and histological markers of inflammation and injury. Results In utero ventilation (IUV) did not alter any blood-gas parameters. IUV significantly increased systemic IL-6 and IL-8 concentrations over the 24 h period compared to CONT. The number of ameboid microglia within the nucleus tractus solitarius and the raphe nucleus increased in VENT fetuses (p < 0.05 for both vs. control). The % area fraction of GFAP + staining was not significantly higher within the preBötzinger complex (p = 0.067) and retrotrapezoid nucleus and parafacial respiratory group (p = 0.057) in VENT fetuses compared to CONT. Numbers of caspase-3 and TUNEL-positive cells were similar between groups. Gene expression (mRNA) levels of inflammation, injury, cell death and prostaglandin synthesis within the brainstem were similar between groups. Conclusion Mechanical ventilation induces a systemic inflammatory response with only moderate inflammatory effects within the brainstem respiratory centres of preterm fetal sheep.